Hypertension and its Associated Factors in a Middle-Aged Population - Bhandari, Tulsi Ram; Paudel, Shishir; Chalise, Anisha; Ojha, Jenny; Paudel, Grish; Khatiwada, Bhushan; Yadav, Uday Narayan (Journal of Nepal Health Research Council, 2024)
Background: Hypertension is a major risk factor for cardiovascular diseases, chronic kidney disease, and dementia. Early detection and management are crucial for preventing these complications. However, many people lack awareness regarding their blood pressure. The study aimed to assess the prevalence of hypertension and its associated factors in rural communities. Methods: This cross-sectional study was conducted among 525 middle-aged (35-60 years) residents of the Rupa Rural Municipality, Nepal, from August to December 2020. Chi-square test and multivariate logistic regression were performed to identify the factors associated with hypertension at a 5% level of significance.Results: More than half (50.9%) of the respondents had normal to elevated systolic pressure, while only one-third (33.9%) had normal to elevated diastolic pressure. Only 47.4% of the hypertensive participants were aware of their hypertensive condition. Being a male (aOR: 1.903; 95% CI: 1.184-3.030), in middle age of 45-55 years (aOR: 2.002; 95% CI: 1.152-3.478), having basic education (aOR: 2.014; 95% CI:1.174-3.455), currently consuming alcohol (aOR: 1.923; 95% CI: 1.095-3.375), and being overweight/ obese (aOR: 1.899; 95% CI: 1.262-2.859) were identified as significant factors associated with hypertension.Conclusions: The studys findings emphasize the urgency of interventions to improve awareness of hypertension and its management to improve health outcomes. Targeted interventions will have an opportunity to reduce the burden of hypertension which is an important risk factor for cardiovascular diseases among the middle-aged population.Keywords: cardiovascular disease; hypertension; Nepal; prevalence; risk factors.